Relatório do estágio curricular supervisionado em Medicina Veterinária- área: sanidade de aves e suínos - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The supervised internship in veterinary medicine was carried out in the area of health of poultry and swine at the Animal Health Laboratory of JBS Foods, located in the city of Seara / SC, accredited by the ABNT NBR ISO / IEC 17025: 2005 standard, in the period from 08/17/15 to 12/02/15, totaling 450 hours. The main objective of the internship was the diagnosis of diseases swine through microbiological and molecular assays, the monitoring of veterinary and public health interest through serological and molecular assays, as well as such as the pre-slaughter research of Salmonella in birds. The internship was carried out under the supervision of Veterinary Physician Anne Caroline Lara, Manager of Animal Health Laboratories at JBS Foods and guidance from Profa. Débora Payão Pellegrini from the Veterinary Medicine course at UNIPAMPA.
Report of the supervised curricular internship in Veterinary Medicine - area: poultry and swine health
Keywords: Medicina veterinária; Suínos; Suinocultura; Porcos; Veterinary medicine; Pigs; Swine; Aves; Birds; CNPQ::CIENCIAS AGRARIAS